A new species of wedgefish Rhynchobatus cooki (Rhinopristiformes, Rhinidae) from the Indo–West Pacific - Last, Peter R.; Kyne, Peter M.; Compagno, Leonard J.v. (Zootaxa, 2016)
A new dwarf wedgefish, Rhynchobatus cooki sp. nov. is described from a single female from a Jakarta fish market (Indonesia) and 11 specimens collected at Jurong fish market (Singapore). First collected in 1934, the broader ichthyological community have been aware of this distinctive but little known ray since the late 1990’s. Rhynchobatus cooki is the smallest of the wedgefishes (to 81 cm TL) and has the lowest vertebral count (fewer than 107 centra). It is also distinguishable from its congeners based on its long, hastate snout, very strongly undulate anterior pectoral-fin margin, coloration and aspects of its squamation. The dorsal coloration is mainly dark and distinctively marked with white blotches, spots and streaks, and has a dark cruciate marking on the interorbit and a prominent white border around the body margin. Unlike most other wedgefish species, the snout tip lacks dark blotches and there is no black pectoral-fin marking. It shares well-developed rostral spines with a much larger Atlantic species (Rhynchobatus luebberti), but these spines are confined to the snout tip (rather than being more numerous and extending in paired rows along the rostral ridges nearly to the eyes). No additional specimens have been observed since 1996, despite an increased recent effort to survey the chondrichthyan fauna of South-East Asia and collect biological data for species, raising concerns over its conservation status.